A new Leptobrachium (Anura: Megophryidae) from the highlands of southeastern Laos - Stuart, Bryan L.; Phimmachak, Somphouthone; Seateun, Sengvilay; Sivongxay, Niane (Zootaxa, 2012)
Twelve species of Leptobrachium are known from Vietnam, Laos and Cambodia, most of which have been described toscience in the past twelve years. Our fieldwork on the Dakchung Plateau of southeastern Laos discovered a small Lepto-brachium with a yellow upper iris that resembled L. buchardi, a species known only by the female holotype from the Bo-laven Plateau of southern Laos. We use our new collections to expand the original description of L. buchardi, and describethe Dakchung species as new. Leptobrachium xanthops sp. nov. is distinguished from its congeners by having small bodysize (males with SVL 44.7, females with SVL 38.8–45.2), the upper one-half of iris and scleral arc pale yellow, a dark venter, and sexually active males without spines on the upper lip.